Low tumor burden is associated with early B-cell reconstitution and is a predictor of favorable outcome after non-myeloablative stem cell transplant for chronic lymphocytic leukemia. Issue 6 (June 2014) - Hebenstreit, Karin; Iacobelli, Simona; Leiblein, Sabine; Eisfeld, Ann-Kathrin; Pfrepper, Christian; Heyn, Simone; Vucinic, Vladan; Franke, Georg-Nikolaus; Krahl, Rainer; Fricke, Stephan; Becker, Cornelia; Pönisch, Wolfram; et al.
Abstract Reconstitution, engraftment kinetics and tumor cell clearance were analyzed after reduced intensity conditioning hematopoietic cell transplant (RIC-HCT) in patients with chronic lymphocytic leukemia (CLL). Patients were transplanted from unrelated (n = 40) or related (n = 10) donors after fludarabine and 2 Gy total body irradiation followed by cyclosporine and mycophenolate mofetil. The vast majority of patients (96%) engrafted with absolute neutrophil count (ANC) > 0.5 × 109/L at day + 22. CLL cells decreased (median 2%, range 0–69%) within 28 days, but disappeared by day + 180 after HCT. Donor T-cell chimerism increased to > 95% at day 56 and donor B-cell chimerism to 94% at day + 360. Overall survival was 51 ± 8%, incidence of progression 37 ± 7% and non-relapse related mortality (NRM) 30 ± 7% at 4 years. The most common causes of NRM were graft-versus-host disease (GvHD) (14%) and sepsis (6%). Disease status at HCT was significantly associated with early B-cell reconstitution (p = 0.04) and with increased risk of relapse/progression in univariate and multivariate analysis (p = 0.022). Tumor cells were undetectable by day + 180, although B-cell reconstitution did not occur until 1.5 years after RIC-HCT. The best predictors for progression-free survival (PFS) and overall survival (OS) were complete response (CR) or first partial response (PR1) and the absence of bulky disease at transplant, respectively.